2016
DOI: 10.5966/sctm.2015-0177
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stem Cells Induce Angiogenesis via Microvesicle Transport of miRNA-31

Abstract: The potential effects of stem cell-released microvesicles (MVs) in proangiogenic therapy were explored. MVs were released from adipose-derived stem cells (ASCs) and were able to increase the migration and tube formation of human umbilical vein endothelial cells. MVs from ASCs, particularly from endothelial differentiation medium-preconditioned ASCs, were found to have elevated levels of microRNA-31 and to promote angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
178
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(199 citation statements)
references
References 67 publications
6
178
0
1
Order By: Relevance
“…Besides, sonic hedgehog overexpressing exosome derived from CD34 + improve cardiac function . Likewise, sonic hedgehog overexpressing exosome derived from T‐lymphocyte induce neoangiogenesis by NO synthesis pathway stimulation . Although such studies are scarce particularly in cardiovascular disease the results are promising and it resting seems that EVs whether as therapeutic vectors or as therapeutic agents are a step forwards in cardiac cell therapy.…”
Section: Application Of Evs Derived From Mscs In Regenerative Medicinementioning
confidence: 99%
“…Besides, sonic hedgehog overexpressing exosome derived from CD34 + improve cardiac function . Likewise, sonic hedgehog overexpressing exosome derived from T‐lymphocyte induce neoangiogenesis by NO synthesis pathway stimulation . Although such studies are scarce particularly in cardiovascular disease the results are promising and it resting seems that EVs whether as therapeutic vectors or as therapeutic agents are a step forwards in cardiac cell therapy.…”
Section: Application Of Evs Derived From Mscs In Regenerative Medicinementioning
confidence: 99%
“…RNA analysis revealed that miRNAs were enriched in adipose‐derived stem cells (ASCs) released MVs, and an underlying mechanism of the pro‐angiogenesis may be the delivery of miR‐31 via MVs from ASCs to ECs. miR‐31 in MVs from ASCs contributed to the migration and tube formation of ECs by targeting and suppressing factor‐inhibiting HIF‐1 …”
Section: The Role Of Mvs Containing Specific Mirnas In Vascular Endotmentioning
confidence: 99%
“…In addition to MVs from MSCs, MVs released from adiposederived stem cells have the same potential application in angiogenic therapy for ischemic diseases, as these MVs were able to increase the migration and tube formation of human umbilical vein endothelial cells [13]. During embryo development, embryonic stem cells (ESCs) employ MVs to communicate with trophoblasts and induce phenotypic change of trophoblasts [14].…”
Section: Intrinsic Function Of Stem Cell Derived Mvsmentioning
confidence: 99%